Hubungan Tingkat Pengetahuan Perawat tentang Time Out dengan Kepatuhan dalam melakukan Time Out di Ruang Operasi Rumah Sakit Balimed Denpasar - Ni Komang Suryathi; N.M.A Sukmandari; M.R.S Wulandari (Bali Health Published Journal, 2021)
A surgical safety checklist is a communication tool for patient safety that is used by the surgical team in the operating room, including the sign in, time out, and sign out process. The time out process aims to prevent patient error, location, and surgical procedures. Therefore, compliance is required in conducting time out. The level of knowledge of nurses about time out is very important because it affects the behavior of nurses in doing time out. This study purposed to determine the correlation between the nurse knowledge level about time out and compliance in doing time out at the Bali Med Hospital, Denpasar. The design used was a descriptive correlation with the cross-sectional approach. The relationship test used the Spearman Rho test. This study involved 31 nurses as a sample with a total sampling technique. The results of research on nurse compliance were mostly 70.9% adherent category and the results for the knowledge level of nurses were mostly 77.4% with a good level. Based on the statistical test with ? = 5%, it was obtained p = 0.000 (p <0.05). It is concluded that there was a significant correlation. The direction of the correlation was positive (+), which means the level of knowledge was followed by the level of nurse compliance in doing time out. This research was expected to be an added reference for nurses in increasing compliance in doing time out.